A Single-Transistor Full-Wave Rectifier - Pookaiyaudom, S.; Watanachaiprateep, C.; Dejhan, K. (My University, 1979)
A simple full-wave rectifier using only a single transistor with two matched resistors has been proposed and the bask performances have been experimentally demonstrated. Copyright © 1979 by The Institute of Electrical and Electronics Engineers, Inc.